PENGARUH GAYA KEPEMIMPINAN, KOMUNIKASI DAN MOTIVASI TERHADAP KEPUASAN KERJA KARYAWAN PT. GUDANG GARAM Tbk KEDIRI - Desi Rosita Dewi; Udik Jatmiko; Bahrul Ulum (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
This study aims to provide empirical evidence of the influence of Variables in this research which consists of Leadership Style (X1), Communication (X2), and Motivation (X3), while the variables influenced are Employee Satisfaction (Y) with sampling techniques based on Determination table for the number of creative tables. The table determines the number of samples from a certain population with an error rate of 10%. Obtained a sample of 90 employees at PT. Gudang Garam Tbk. Data obtained through questionnaires,interviews and observations. Based on the test results show that the leadership style positively significant effect on job satisfaction. Communication has no significant effect on job satisfaction. Motivation has a significant positive effect on job satisfaction. Simultaneously the variables of Leadership Style, Communication and Motivation influence Job Satisfaction which can be proven with a Fcount value of 60.5141> Ftable 2.74 with a significance value (sig) of 0.000 which is much smaller than 0.05.